Impact of diffuse idiopathic skeletal hyperostosis on quality of life and locomotive syndrome in community-dwelling older adults: the Yakumo study - Kazuma Ohshima; Hiroaki Nakashima; Naoki Segi; Sadayuki Ito; Jun Ouchida; Yasuhiko Takegami; Shinya Ishizuka; Ippei Yamauchi; Yukiharu Hasegawa; Kenta Murotani; Shiro Imagama (Scientific Reports)
Abstract Diffuse idiopathic skeletal hyperostosis (DISH) is a common disease in older adults that causes extensive spinal ankylosis. However, its impact on quality of life (QOL) and locomotive syndrome (LS) remains unknown. Thus, we aimed to evaluate the DISH effect on QOL and LS in community-dwelling middle-aged and older adults. Data of community volunteers who attended a health checkup in 2018–2019 were assessed. A total of 455 subjects were included. Whole spine lateral radiographs were obtained to detect DISH according to the Resnik criteria. QOL was evaluated using SF-36 and EQ5D HUSV. LS was evaluated using the stand-up and two-step tests and GLFS-25. Multivariate regression analysis was performed, adjusting for sex, age, body mass index, and knee osteoarthritis. Additionally, a sex-stratified analysis was performed. DISH was detected in 83 (18.2%) participants. Multivariate analysis demonstrated that DISH was significantly associated with low EQ5D HSUV. Multivariate analysis in men demonstrated that DISH was associated with low PCS, low EQ5D HSUV, high LS stage. Multivariate analysis in women demonstrated that DISH was not associated with any QOL or LS. DISH may be associated with a poor QOL. Additionally, DISH is more common and produces a greater clinical impact in men than in women.